Antioxidant defense response induced by Trichoderma viride against Aspergillus niger Van Tieghem causing collar rot in groundnut (Arachis hypogaea L.). (February 2016) - Gajera, H.P.; Katakpara, Zinkal A.; Patel, S.V.; Golakiya, B.A.
Abstract: The study was conducted to examine the antioxidant enzymes induced by Trichoderma viride JAU60 as initial defense response during invasion of rot pathogen Aspergillus niger Van Tieghem in five groundnut varieties under pot culture. Seed treatment of T. viride JAU60 reduced 51–58% collar rot disease incidence in different groundnut varieties under pathogen infected soil culture. The activities of the antioxidant enzymes, viz., superoxide dismutase (SOD, EC 1.15.1.1), guaiacol peroxidase (GPX, EC 1.11.1.7) and ascorbate peroxidase (APX, EC 1.11.1.11), elevated in response to pathogen infection, in higher rate by tolerant varieties (J-11 and GG-2) compared with susceptible (GAUG-10, GG-13, GG-20) and further induced by T. viride treatment. Trichoderma treatment remarkably increased the 2.3 fold SOD, 5 fold GPX and 2.5 fold APX activities during disease development in tolerant varieties and the same was found about 1.2, 1.5 and 2.0 folds, respectively, in susceptible varieties. Overall, T. viride JAU60 treated seedlings (T3 ) witnessed higher activities of SOD (1.5 fold), GPX (3.25 fold) and APX (1.25 fold) than pathogen treatment (T2 ) possibly suggest the induction of antioxidant defense response by Trichoderma bio-controller to combat oxidative burst produced by invading pathogen. Highlights: Trichoderma viride JAU60 would be the best eco-friendly agent to reduce Aspergillus niger infection in groundnut rhizosphere. T. viride JAU60 induced an early first line antioxidant response against the invading pathogen in groundnut. Ascorbic acid did not augment upon infection in susceptible varieties. Enzymes SOD, GPX, APX protect the tolerant varieties (J-11 and GG-2) upon rot infection. T. viride induced defense response with the stronger uplifting enzymes in tolerant plants.